Tomotherapy-like versus VMAT-like treatments: a multicriteria comparison for a prostate geometry. - Pardo-Montero, J; Fenwick, J (2012)
PURPOSE: To perform a methodological comparison of volumetric modulated arc therapy (VMAT)-like and tomotherapy-like techniques for a prostate geometry, exploring the dependence on machine, delivery, and optimization parameters of cost function values optimized for each technique. METHODS: A gradient-descent algorithm is used to optimize tomotherapy-like treatments, while VMAT-like optimization is carried out using a direct-aperture simulated annealing algorithm with 180 control points equispaced at 2° angles. Dose distributions are linked to fluences via a three-dimensional double-gaussian pencil beam model. Plans are optimized for a prostate geometry, outlined according to the CHHiP protocol. The cost function used for optimization contains ten simple functions, each of which describes a single planning objective. These functions are split into three structure groups according to whether they are used to control PTV, rectal or bladder dose levels. Different optimizations have been performed by varying the relative weights of each of these structure groups, exploring in this way a three-dimensional Pareto front. Plan quality is studied according to the value of the optimized cost function and the relative Euclidean distance between the components of the cost function and those of the nearest plan lying on a reference Pareto front obtained for tomotherapy-like plans generated using a 1 cm fan-beam width and 1/3 pitch. RESULTS: The quality of tomotherapy-like optimization depends on the fan-beam width, s, and rotation pitch, p, used to deliver the treatment. These values together define the effective longitudinal resolution with which fluence can be modulated, and lower cost function values are obtained for treatments optimized with tighter pitches and narrower fan-beam widths (higher modulation resolution). On the other hand, the cost function values of VMAT-like optimizations depends on the optimization running time, leaf displacement constraints, and number of arcs employed, as well as on the size of the beamlets used in the optimization (a change in leaf width from 5 to 10 mm clearly worsens the value of the objective function, but only a marginal improvement is observed when the leaf movement discretization step is reduced from 5 to 5/3 mm). However, for no combination of these parameter values did VMAT-like optimizations match the cost function values of optimized tomo-like plans obtained for s = 1 cm and p = 1∕3 (or 1/2). This is the case all across the Pareto front. On the other hand, cost function values of VMAT-like plans are generally lower than those of optimized tomotherapy-like plans obtained for s = 2.5 cm. CONCLUSIONS: Tomotherapy-like plans created for the prostate geometry using a 1 cm fan-beam width and pitches of 1/3 or 1/2 have lower cost function values than VMAT-like plans, although the associated dosimetric improvements are quite small, both techniques generating very good dose distributions. When a 2.5 cm wide fan-beam is used for tomotherapy-like treatments the pattern is reversed, the tomotherapy-like plans having higher cost functions than the VMAT-like ones.